The taste of heat: How humoral qualities act as a cultural filter for chemosensory properties guiding herbal medicine. (23rd February 2017) - Geck, Matthias S.; Cabras, Stefano; Casu, Laura; Reyes García, Alberto J.; Leonti, Marco
Abstract: Ethnopharmacological relevance: Organoleptic properties, and more specifically chemosensory cues, have been shown to guide therapeutic applications of medicinal plants. Humoral qualities, on the other hand, are widely believed to be an abstract concept, mainly applied post hoc to validate therapy. However, the nexus between humoral qualities, chemosensory properties, and medicinal plant uses has never been systematically assessed. Aim of the study: To systematically analyse the correlations between chemosensory properties, humoral qualities, and medicinal uses of selected botanical drugs. Methods: The issue was approached experimentally via an organoleptic testing panel, consisting of Zoque healers in Chiapas, Mexico. The healers smelled and tasted 71 selected herbal drugs and subsequently commented on their humoral qualities and therapeutic uses. The resulting dataset is analysed for correlations between these variables using Bayesian statistics. Qualitative data on the characteristics and role of the hot-cold dichotomy complement the quantitative analysis, facilitating meaningful interpretation. Results and discussion: The results reproduce and extend the findings of previous studies, which established specific correlations between chemosensory cues and nosological units. The key predictors of drugs' therapeutic uses, however, are their humoral qualities, which are themselves conditioned by taste and smell. These findings appear to be valid for drug samples known to the participants as well as for unfamiliar samples. Thus, this study establishes the role of the hot-cold dichotomy as an important cultural filter connecting organoleptic properties and therapeutic uses of herbal drugs. Conclusions: There is considerable cross-cultural consensus in Mesoamerica for the specific correlations described in this study. Given the continued pervasiveness of the hot-cold dichotomy, humoral qualities and the underlying organoleptic properties ought to be increasingly considered in the design of pharmaceutical products as well as public health strategies. Such culturally appropriate adjustments may considerably improve the perceived quality and effectiveness of healthcare. Graphical abstract: